Proclus on nature : philosophy of nature and its methods in Proclus' Commentary on Plato's Timaeus - Martijn, Marije. (Philosophia Antiqua, 2010)
Of Proclus' immense philosophical system, the part concerning the natural world may well be the most fascinating. Traditional scholarship tends to downplay that part of Neoplatonism, in favour of idealism, but recently this attitude is changing. This study contributes to that development by showing how Proclus' natural philosophy relates to theology, while remaining a science in its own right. Starting from his Commentary on Plato's Timaeus, it presents a revision of Proclus' metaphysics of nature and provides new insight into his surprisingly peripatetic philosophy of science, the role of mathematics, and the nature of discourse in natural philosophy. This book will be of interest both to students of the Platonic tradition, and to historians of natural science, metaphysics and epistemology.